Simulation of Marine Bio-Composite Using Empirical Data Combined with Finite Element Technique - Roy, Himanshu; Pahlevani, Farshid; Cholake, Sagar; Echeverria, Claudia; Banerjee, Amborish; Sahajwalla, Veena (Journal of composites science, 2018)
After development of world-first marine bio-composite from 100% waste materials, the necessity of obtaining a simulation tool to predict the performance of this novel material under different conditions has arisen. This study examines the combination of empirical optimization and finite element simulation method as an economic and time-effective tool to predict the mechanical performance of novel complex bio-composite mixtures at the design phase. Bio-composite panels were manufactured introducing marine bio-fillers as secondary reinforcements in a wood–polypropylene particulate blend, from 100% waste resources. The particulate panels were subject to tensile test for mechanical characterization. Based on these results, some of the necessary parameters for finite element simulation has defined empirically and a finite element model was developed utilizing ANSYS software, performing a simulation series. Post-processing of the simulation results was carried out to predict the deformation behavior of the material during the three-point bending test. To validate this technique of material definition, the simulated static bending test results were verified with factual physical tests, and both techniques were well in accordance with each other. This simulation method demonstrated reliable feedback on the behavior of materials for the development of innovative complex materials. Therefore, the time invested, materials used and experimental procedures can be significantly reduced, having significant economic benefits for research and industrial projects.